THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN COMPLETING LAND CERTIFICATE PROCESSING AT BADAN PENTANAHAN NASIONAL (BPN) OFFICE IN MEDAN CITY - Divi Sahfira; Wiro Oktavius Ginting (Jurnal Scientia, 2023)
Employee performance is important for an employee, especially in completing the processing of land certificates. To create optimal performance, the leader is tasked with creating good organizational conditions for the activities of members of the organization, so that they can achieve organizational performance targets. In accordance with the results of the Performance Assessment of employees of the Medan City BPN office there is a phenomenon in 2021, there are several indicators that have decreased from the previous year, namely starting from the elements of loyalty, responsibility, obedience, honesty, cooperation, and leadership style by 1.3% up to 2.8% from 2021. The results of the study show that leadership style partially has a significant effect on the performance of the Medan City BPN office employees. Research recommendations, to improve the performance of BPN Medan City office employees, a leader must prioritize elements of the right leadership style in order to encourage the performance of Medan City BPN office employees.